IGF2BP3 May Contributes to Lung Tumorigenesis by Regulating the Alternative Splicing of PKM - Xueqing, Huang; Jun, Zhang; Yueqiang, Jiang; Xin, Liao; Liya, Hu; Yuanyuan, Fang; Yuting, Zhang; Hao, Zeng; Hua, Wu; Jian, Liu; Tiejun, Yin (Frontiers in Bioengineering and Biotechnology, 2020)
RNA binding proteins (RBPs) play a key role in genome regulation. Here we report the post-transcript regulation of IGF2BP3, which belongs to the insulin-like growth factor 2 mRNA binding protein family. We used iRIP-seq and RNA-seq to analyze the transcript regulation and alternative splicing on IGF2BP3 treated with overexpression cells and control. Overexpressed IGF2BP3 has broadly increased genes expression which involved in G-protein coupled receptor signaling pathway, positive regulation of cell proliferation, and signal transduction. IGF2BP3 regulated alternative splicing of multiple genes mainly clustered at response to hypoxia, negative regulation of transcription, and embryonic development. This study first provides alternative splicing analysis on transcription level of IGF2BP3 regulation, which laid the foundation for later research on IGF2BP3 critical functions.